2020
DOI: 10.1186/s12941-020-00358-y
|View full text |Cite
|
Sign up to set email alerts
|

Successful recovery of COVID-19 pneumonia in a patient from Colombia after receiving chloroquine and clarithromycin

Abstract: Background: COVID-19 pandemics is a challenge for public health and infectious diseases clinicians, especially for the therapeutical approach that is not yet adequately defined. Amid this situation, investigational agents are being used, including chloroquine. We report here the clinical features and therapeutic course of the first reported patient with confirmed COVID-19 pneumonia that recovered in Colombia, after the use of chloroquine and clarithromycin. Case presentation:A 34-year-old male, returning from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 45 publications
0
47
0
3
Order By: Relevance
“…Other small experiences appeared in the scientific literature later on in a similar direction. One study in Taiwan, reported two cases with community-acquired pneumonia caused by severe acute respiratory syndrome coronavi- In Colombia, as published, one patient received clarithromycin instead of azithromycin, in combination with chloroquine with the successful recovery of COVID-19 pneumonia, without any side adverse effects and become negative for the SARS-CoV-2 infection, as observed in the RT-PCR test [85].…”
Section: Other Studies Indicating That Clarithromycin Is a Good Optiomentioning
confidence: 95%
“…Other small experiences appeared in the scientific literature later on in a similar direction. One study in Taiwan, reported two cases with community-acquired pneumonia caused by severe acute respiratory syndrome coronavi- In Colombia, as published, one patient received clarithromycin instead of azithromycin, in combination with chloroquine with the successful recovery of COVID-19 pneumonia, without any side adverse effects and become negative for the SARS-CoV-2 infection, as observed in the RT-PCR test [85].…”
Section: Other Studies Indicating That Clarithromycin Is a Good Optiomentioning
confidence: 95%
“…During the preparation of this manuscript, the first reports on CQ/HCQ effects in COVID-19 patients were published ( 3 , 111 , 114 116 ). However, there was extreme variability in study design, study population, time after symptom onset, sample size, CQ/HCQ dosage and duration of treatment, concurrent administration of other molecules, while the methodology often did not meet the usual standards ( 117 ), leaving the reader without clear, comparable data.…”
Section: Cq/hcq and Covid-19: Pros And Cons In The Context Of Immunommentioning
confidence: 99%
“…In vitro and clinical data suggest that CQ/HCQ could be useful as a means of preventative control of type I IFN-induced immune activation in SARS-CoV-2 patients ( 116 , 121 ), although other randomized, controlled studies questioned these findings ( 122 , 123 ). Recent reports suggest that CQ/HCQ may not act as a rescue medication for severe cases or advanced forms with multiorgan failure ( 124 ).…”
Section: Cq/hcq and Covid-19: Pros And Cons In The Context Of Immunommentioning
confidence: 99%
“…Muitos estudos apoiam o uso clínico da combinação de medicamentos, especialmente da hidroxicloroquina e azitromicina, principalmente no estágio inicial da infecção por COVID-19, antes que os pacientes desenvolvam síndrome do desconforto respiratório. Além disso, alguns países precisam realizar estudos sequenciais e filogenéticos, pois seus isolados podem divergir de outros SARS-CoV-2 (Andreani J;Millán-oñate, J;.…”
Section: Soluções Obtidas Para Eficácias De Novos Antibióticosunclassified